Computing in Research and Development in Africa : Benefits, Trends, Challenges and Solutions - Gamatié, Abdoulaye (Springer International Publishing : Imprint: Springer, 2015)
This book describes the trends, challenges and solutions in computing use for scientific research and development within different domains in Africa, such as health, agriculture, environment, economy, energy, education and engineering. The benefits expected are discussed by a number of recognized, domain-specific experts, with a common theme being computing as solution enabler. This book is the first document providing such a representative up-to-date view on this topic at the continent level.   • Discusses computing for scientific research and development on the African continent, addressing domains such as engineering, health, agriculture, environment, economy, energy, and education; • Describes the state-of-the-art in usage of computing to address problems in developing countries pertaining to health, productivity, economic growth, and renewable energy; • Offers insights applicable to all developing countries on the use of computing technologies to address a variety of societal issues.